Comparison of Efficacy of Sofosbuvir & Daclatasvir with Sofosbuvir and Velpatasvir in Achieving SVR in Patients of Chronic Hepatitis C with Genotype 3 - Tanveer Ahmed, Omer Hassaan Aftab Ahmad, Muhammad Bilal, Sher Alam, Shirjeel Zaheer, Zaid Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hepatitis C virus of chronic nature has been appreciated globally to be a major source of hepatic carcinomas and other abnormalities associated with liver function. The epidemiological data on the prevalence of the Hepatitis C virus shows a trend of 71 million people being affected by the disease globally with an annual mortality rate of 3.5 to 5 million death. Pakistan showed a prevalence of up to 8.2% which is among the most common incidents in countries. Since genotype 3 is the most common variant in Pakistan there remains a literature gap that evaluates the effectiveness of velpatasvir plus sofosbuvir and daclatasvir plus sofosbuvir and compares their efficiency. This study will aim to compare the efficiency of sofosbuvir and velpatasvir with sofosbuvir and daclatasvir. Place and Duration: The study was conducted at the department of Gastroenterology in PIMS Hospital, Islamabad during the period from 21st June 2020 to 20th June 2021. Methodology: The total number of participants recruited in this study was 1000. Participants were recruited after meeting the inclusion and exclusion criteria. The participants were then divided into two groups of n=500 with group one receiving therapy by Sofosbuvir and Daclatasvir and group two receiving a therapy regimen consisting of Sofosbuvir/Velpatasvir. Both the groups underwent therapy for the same amount of time (12 weeks). Before initiation of regimens, patients underwent baseline testing including blood screens, biochemical screens, fibro scans, genotypes, and PCR. These tests we basis for evaluation before and after the treatment. The goal was to achieve detection of no HCV RNA virus at the end of the management protocol. Due to known complications in patients presenting with cirrhosis, the duration of the drug was extended up to 24 weeks. For the patients who presented with relapse of chronic HCV, the end treatment success was measured by HCV RNA less than or equal to 25 IU/ml after 12 weeks of drug use Results: Around 98% of the participants receiving sofosbuvir and velpatasvir management retreatment patients reached the end of treatment assessment and showed sustained viral response and at the end of treatment a small amount of 2% of the participants were found to relapse. The number of patients who reached the end of treatment was 96.2% and 3.8% discontinued the treatment which is more than that compared to the sofosbuvir -velpatasvir regimen. The rate of poor response to treatment management in the sofosbuvir -the daclatasvir group was more than that of the sofosbuvir -velpatasvir group in comparison of 4.3% to 5.8%. This group showed a similar rate of relapse which is 2%. Conclusion: The results of this study showed that sustained viral response was higher in the group managed by sofosbuvir and velpatasvir in comparison to sofosbuvir and daclatasvir. Furthermore, patient compliance to treatment was better in the group treated with sofosbuvir and velpatasvir in comparison to another group. It was also established that the group managed by sofosbuvir and daclatasvir showed a higher incidence of drug adverse events